THE FUTURE OF AFRICAN THEOLOGY IN THE GLOBAL CHRISTIAN CONFIGURATION: PROSPECTS AND CHALLENGES - ALEXANDER NDUBUISI ABONYI (International Studies Journal)
African theology is one of the emergent theologies that emanated from the stable of the Majority World nations, often generically referred to as Third World Theologies. They are emergent because they have a rather recent history compared to the older theological systems from the West. One characteristic feature of these theologies is that they are reactionary in nature. In the case of African theology, African theologians feel that Western missionaries denigrated and rubbished African traditional religions and culture, dubbing them to be primitive, satanic and archaic. In response, African theologians came up with a system of theology that uses African religion and cultural categories as its point of departure. The system is fraught with lots of biblical and theological pitfalls. African theology has proven to be syncretistic as it welds two dichotomous systems together. Therefore, the study is extending the existing premise of African theology by suggesting ways it can be more relevant to the Christian world. The study applied both the historical and phenomenological methodologies. It used the historical methodology to gather the historical evidence of the evolution of African theology and the phenomenological methodology to analyse it. The study found out that the anti-Western stance of African theology has alienated it from mainstream Christianity. The study has enriched the existing literature in the study area by positing that African theology should approach its theological system from a more biblio-centric premise so that it can remain true to historic Christianity. It can then argue its position from a pedestal of strength and avoid the accusation of being racially inclined.